The Implementation and Urgency of Gamification in Enhancing Motivation and Learning Outcomes of Elementary School Students: A Systematic Literature Review - Nizhomi, Bestiana; septiani, devi (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2025)
This study aims to analyze the trends, psychological impacts, and academic effectiveness of implementing gamification methods at the Elementary School (SD) level using the Systematic Literature Review (SLR) method. In the era of the industrial revolution 4.0 and society 5.0, conventional learning methods often fail to maintain the attention of "Generation Alpha" students who are accustomed to digital stimulation. Data were collected from Google Scholar, Garuda, and DOAJ databases spanning the last 10 years (2015-2025). Based on selection using the PRISMA protocol, 20 main articles were thematically analyzed. The review results show three main findings: (1) There is an evolution of gamification media from desktop/offline applications to cloud-based platforms and AI integration; (2) Gamification significantly increases intrinsic motivation through the fulfillment of Self-Determination Theory needs (competence, autonomy, relatedness); (3) There is a consistent improvement in cognitive learning outcomes, especially in Mathematics and Science subjects, as well as critical thinking skills. This study concludes that gamification is an urgent pedagogical necessity to create joyful learning relevant to the characteristics of today's students.